PERAN INOVASI SISTEM DALAM MENINGKATKAN MANAJEMEN KINERJA UNTUK COMPETITIVE ADVANTAGE DI PT. TELKOM AKSES REGIONAL IV - Linayli Fauzia Kamal; Sa'adatu Miftahul Jannah; Agustin Widiyawati; Kevin Zaqi Maulana; Ratih Pratiwi (Sekolah Tinggi Ilmu Ekonomi AMA Salatiga, 2022)
This study aims to prove and explain the Role of System Innovation in improving Performance Management for Competitive Advantage at PT. Telkom Regional Access IV. The research method used is quantitative research methods. The research object consists of system innovation, performance management and competitive advantage. The research subjects were 34 employees in all divisions at PT. Telkom Regional Access IV. Data were collected through observation and questionnaires.